Pharmacokinetic interaction of intravenous fentanyl with ketoconazole - Ziesenitz, Victoria C.; Skopp, Gisela; Haefeli, Walter E.; Mikus, Gerd (Journal of clinical pharmacology, 2015)
Fentanyl is primarily metabolized by CYP3A, but has also been suggested to act as a weak inhibitor of CYP3A. We investigated the influence of CYP3A inhibition by ketoconazole on the pharmacokinetics of intravenously administered fentanyl and the effect of fentanyl on CYP3A activity. A prospective, open-label, randomized, monocentre, crossover study was conducted in 16 healthy volunteers. They received fentanyl alone (5 microgram per kilogram) or fentanyl plus ketoconazole (200 milligram orally B.I.D. over 2 days). Naloxone (2 × 0.2 milligram i.v.) was given simultaneously with fentanyl to mitigate any opioid effect. Midazolam was administered as a CYP3A probe drug. Fentanyl and its metabolites were quantified by LC/MS/MS in blood and urine samples obtained over 24 hour. Exposure of fentanyl (AUC0-∞) was significantly increased to 133% and systemic clearance was reduced to 78% by ketoconazole, norfentanyl formation was significantly delayed and partial metabolic clearance decreased to 18%. Fentanyl had no influence on midazolam exposure and CYP3A activity whereas ketoconazole decreased CYP3A activity to 13%. Although fentanyl N-dealkylation is substantially inhibited by ketoconazole, exposure of fentanyl itself increased by one third only. Clinically fentanyl dosage adjustments may become necessary when ketoconazole or other strong CYP3A inhibitors are given simultaneously. Fentanyl itself does not influence CYP3A activity.